Sea surface temperature and salinity seasonal changes in the western Solomon and Bismarck Seas. Issue 4 (25th April 2014) - Delcroix, Thierry; Radenac, Marie‐Hélène; Cravatte, Sophie; Alory, Gaël; Gourdeau, Lionel; Léger, Fabien; Singh, Awnesh; Varillon, David
Abstract We analyze mean and seasonal change of Sea Surface Temperature (SST) and Salinity (SSS) in the Solomon and Bismarck Seas, using 1977–2009 in situ data collected from Voluntary Observing Ships. Covariability of these two variables with surface wind, altimeter‐derived and model‐derived horizontal currents, precipitation, and Sepik River discharge are examined. SST and SSS show large annual oscillations in the Solomon Sea, with the coldest and saltiest waters occurring in July/August mainly due to horizontal advection. In contrast, they show large semiannual oscillations in the Bismarck Sea. There, the coldest and saltiest waters happen in January/February, when the northwest monsoon winds drive coastal upwelling, and in July/August, when the New Guinea Coastal Current advects cold and high‐salinity waters from the Solomon Sea through Vitiaz Strait. The low SSS values observed in April/May, stuck between the January/February and July/August SSS maxima, are further enhanced by the Sepik River discharge annual maximum. A high‐resolution model strengthens the conclusions we derive from observations. The impacts of ENSO on SST and SSS are also discussed with, for instance, saltier‐than‐average and fresher‐than‐average waters during the 2002–2003 El Niño and 2007–2008 La Niña, respectively.